Predicting the Entrepreneurship Intention of Undergraduate University Students in Malaysia: A Comparison Study - MOHD NOOR, NURUL HIDAYANA; MALEK, EQMAL NAQIB; YAACOB, MAHAZRIL ‘AINI; OMAR, NORALINA (Trends in Undergraduate Research, 2021)
Entrepreneurship allows students to learn beyond their chosen field of study and provides an interdisciplinary work and development environment. This study aims to examine the influence of attitude towards behavior, subjective norm, and perceived behavioral control on entrepreneurship intention among Malaysian undergraduates. In addition, this study intends to compare the influence of attitude towards behavior, subjective norm, and perceived behavioral control on entrepreneurship intention between diploma and bachelor’s degree students. Based on a quantitative approach, primary survey data were collected from 400 undergraduate students at a public university using convenience sampling to limit bias. The findings in this study indicate that attitude towards behavior, subjective norm, and perceived behavioral control are significantly positively related to entrepreneurship intention for diploma and bachelor’s degree students. Notwithstanding this, the multiple regression results reveal that the strongest predictor of entrepreneurship intention for diploma students is the subjective norm while perceived behavioral control is the main predictor that affects entrepreneurship intention for bachelor’s degree students. These findings contribute to the entrepreneurial intention literature by applying the theory of planned behavior in Malaysia with valuable practical implications for the management of universities and the government.